2013
DOI: 10.1080/02615479.2013.855193
|View full text |Cite
|
Sign up to set email alerts
|

Outness among LGBTQ Social Work Students in North America: The Contribution of Environmental Supports and Perceptions of Comfort

Abstract: This study examines various environmental factors that may impact a lesbian, gay, bisexual, transgender, or queer (LGBTQ) social work student's level of 'outness' (disclosure) with regard to their sexual orientation or gender identity. An internet-based survey was conducted, comprised of LGBTQ undergraduate and graduate students from social work programs across North America (n ¼ 1,018). Utilizing Pearson's chi square analysis, significant associations correlated between outness and the following six areas: (1… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
9
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 30 publications
(9 citation statements)
references
References 43 publications
0
9
0
Order By: Relevance
“…LGB students experience a variety of classroom settings, which can range from supportive to hostile (Longerbeam et al, 2007). Although studies of LGBTQ social work students tend to have small samples, it has been found that the lack of course material on LGBTQ populations, specific supports for LGBTQ students, as well as out LGBTQ faculty, field instructors and staff most inhibit their ability to learn within the educational environment (Dentato et al, 2013;Messinger, 2007;Hylton, 2006;Newman et al, 2009;Fairtlough et al, 2012). Despite these challenges, there remains a dearth of scholarship that specifically examines the RTP of social work students with LGBTQ populations.…”
Section: Factors Associated With Students' Rtp With Lgbt Populationsmentioning
confidence: 99%
“…LGB students experience a variety of classroom settings, which can range from supportive to hostile (Longerbeam et al, 2007). Although studies of LGBTQ social work students tend to have small samples, it has been found that the lack of course material on LGBTQ populations, specific supports for LGBTQ students, as well as out LGBTQ faculty, field instructors and staff most inhibit their ability to learn within the educational environment (Dentato et al, 2013;Messinger, 2007;Hylton, 2006;Newman et al, 2009;Fairtlough et al, 2012). Despite these challenges, there remains a dearth of scholarship that specifically examines the RTP of social work students with LGBTQ populations.…”
Section: Factors Associated With Students' Rtp With Lgbt Populationsmentioning
confidence: 99%
“…Students’ level of outness may be shaped by their own comfort about their gender identity and their perceptions of others around them (Dentato et al 2013). Prior work has found a clear connection between outness and relationships with faculty, staff, peers, and mentors (Dentato et al 2013; Garvey and Inkelas 2012; Garvey and Rankin 2015b; Renn 2007). Respondents’ open-ended comments confirm the relevance of relationships for outness and climate perceptions, with many students discussing interpersonal interactions as central to their campus climate perceptions and identity disclosure.…”
Section: Discussionmentioning
confidence: 99%
“…For example, campus-wide policies to protect marginalized students can be developed proactively (Alessi et al, 2017;Chinell, 2011;Clark, Kleiman, Spanierman, Isaac, & Poolokasingham, 2014). Campus leadership can help to support LGBTQ+ affirming programming (Dentato, Craig, Messinger, Lloyd, & McInroy, 2014). Student-led organizations and associations are also critical to campus climate (Dentato et al, 2014;McCabe, 2009).…”
Section: Campus-wide and Classroom Interventionsmentioning
confidence: 99%
“…Campus leadership can help to support LGBTQ+ affirming programming (Dentato, Craig, Messinger, Lloyd, & McInroy, 2014). Student-led organizations and associations are also critical to campus climate (Dentato et al, 2014;McCabe, 2009). Recognition from peers about the social pain of microaggressions may be particularly meaningful for students in emerging adulthood (Byers, 2013(Byers, , 2016.…”
Section: Campus-wide and Classroom Interventionsmentioning
confidence: 99%